A name, a destiny: an onomastic in Nelson Rodrigues’ fictional works - Rabelo, Adriano de Paula (Via Atlântica, 2020)
Characters’ names are one of the most important keys to interpreting a fictional work. They can even determine the course of the story’s action. Especially, they express a lot about who these characters are, why they do what they do, how they represent aspects of a specific social reality. In the plays, novels, short stories and newspaper serial narratives by Nelson Rodrigues, a writer who was fully aware of the expressive power of names, to the point of frequently reflecting on this issue in his essayistic newspaper columns, his characters’ names are one of the aspects the reader or viewer of the his works should pay close attention. This article results from an extensive survey of Rodrigues’ characters names, classifying them into categories and analyzing their meanings, their peculiarities, and their relation with the personalities they name.